Comparative statistical analysis of incidental dolphin mortality, during fishing trips of the Mexican purse seine tuna fishery in the Eastern Pacific Ocean recorded by two scientific observer programs - Dreyfus-Leon, Michel J.; Solana-Arellano, Elena (Revista de Biología Marina y Oceanografía, 2020)
Scientific observer programs in fisheries are being deployed worldwide in order to obtain robust data for fishery studies, and in relation to its interaction with target and bycatch species. A comparison between two observer programs in Mexican purse seine tuna fishery in the Eastern Pacific ocean is performed considering the incidental mortality per trip as a metric recorded by both observers programs from 1999 to 2016. A Bayesian t-test approximation was used for the comparison between the two methods since, due to its probabilistic nature reduces uncertainty. The analysis showed a very low probability of differences for the estimated bycatch rate between both programs.